Pengaruh Latihan Power Tungkai Melalui Metode Box Jump terhadap Tinggi Loncatan Smash Bola Voli pada Peserta Ekstrakulikuler SMK Negeri 1 Kuningan - Muhammad Helmi; Didi Muhtarom (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study was conducted with the aim of determining the extent to which leg power training through the box jump method influences the increase in volleyball smash jump height in extracurricular participants at SMK Negeri 1 Kuningan. Volleyball requires good physical abilities, especially explosive leg muscle power, because this skill plays a very important role in performing the smash movement as the main form of attack. One form of training that is believed to be able to increase explosive power is box jump training, which is a type of plyometric training that emphasizes repeated jumping movements with high intensity. The research method used was an experiment with a one group pretest-posttest design. The study involved a sample group consisting of 15 students, taken using a total sampling technique from all volleyball extracurricular members. The data collection instrument used the vertical jump smash test according to Ali Maksum. The test was conducted in two stages, namely before treatment (pretest) and after treatment (posttest). The results of data analysis showed a significant increase after being given treatment in the form of box jump training. This is evidenced by a significance value (p) of 0.000 which is smaller than 0.05, so it can be concluded that there is a real difference between the pretest and posttest results. In other words, box jump training has been shown to be effective in increasing smash height. These findings indicate that training programs designed to incorporate plyometric elements, particularly box jumps, can optimally develop leg muscle explosive power. Therefore, this study recommends that coaches and sports teachers incorporate box jumps as a primary training component in volleyball skills development programs, significantly improving players' offensive performance.